A New Species of Nazeris Fauvel from Guangdong, China (Coleoptera, Staphylinidae, Paederinae) - Sun, Wanwan; Jiang, Feiyan; Guo, Jingjing; Zhang, Tianxin; Liu, Zhiping (Zootaxa, 2023)
A new species, Nazeris qilinshanensis Guo, Liu & Sun sp. nov. from Qilinshan, Guangdong province is described and illustrated. The external morphological characteristics and genitalia of the new species are described in detail and illustrated. The complete mitochondrial genome of N. qilinshanensis was sequenced and placed in a phylogenetic context. Phylogenetic analysis based on mitochondrial genomes showed that N. qilinshanensis forms a clade with Astenus lyonessius (Joy, 1908), within Lathrobiini.